Perancangan Augmented Reality untuk Peta Topografi - Yosanny, Agustinna; Ismail, Muhammad; Said, Handoko (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Topography is the science about the earth's surface and other objects such as planets, satellites, and asteroids. Topography is studied at school and is found quite difficult to understand because it requires imagination to understand the meaning of contour maps as well as the lines. To motivate students in learning topography,we design an learning application of interactive topographic map with 3D features using Augmented reality technology. In this research we implement analysis and design method. The result achieved is a learning topographic map application based on augmented reality. The conclusion that can be drawn is the teaching and learning of topography can be more interesting with 3D features so that students can more easily recognize the meaning of contour lines in a topographic map.